Analisis Model Simulasi Berbasis Algoritma Dalam Peningkatan Kompetensi Manajemen Kesiagaan Bencana Perawat Komunitas Kota Surakarta - Sunarto Sunarto; Addi Mardi Harnanto (Poltekkes Kemenkes Surakarta, 2019)
Background: The Republic of Indonesia is a country that is vulnerable to disasters. Disaster preparedness is an important component in disaster management in order to reduce mortality or morbidity. One component of the community component that plays a role in disaster preparedness is health workers including nurses. The role and competence of disaster management must be considered and enhanced for community nurses to ensure the safety of the community in dealing with disasters starting from the prevention phase, the mitigation phase, the preparedness phase, the emergency response phase and the recovery phase. Algorhythms is an effective method in increasing understanding in a training or simulation.This study was conducted to analyze the effectiveness of the algorithm based algorithm can increase competency of disaster preparedness management in community nurses in the city of Surakarta. Methods: This type of research is a comparative experimental study with a pretest-post test with control group design. The population in this study were all community nurses in the city of Surakarta as many as 110 people. The sampling technique was a total sampling of 97 people (88%). Data is tested by Difference Test. Results: There was an increase in the value of roles and competencies in all groups. Difference in value improvement in the treatment group is (role = 2.56 and competence = 2.76). While the increase in value in the control group is (role = 2.05 and competence = 1.88). Value of P = 0.00. Conclusion: There are significant differences in the value of roles and competencies between the treatment and control groups. Increasing the value of the role and competence of the simulation group with algorithm learning is higher than the control group.